Structure elucidation of transformed metabolites from bioactive compounds using microbial transformations as a green synthetic tool / Mohd Zaimi Mohd Noor - Mohd Noor, Mohd Zaimi (2014)
Biotransformation is considerably one of the foundational pillars of green chemistry practice. Chemical modification through biotransformation are performed in mild condition, room temperature, in water based syntheses pot and can provide efficient alternative to chemical syntheses as the microbial transformation can reduce the use and generation of hazardous substances. Biotransformation is an important tool for modification of organic compounds, especially natural product with complex structures like steroids. Microorganisms whole cell based biotransformation have been carried out by using steroidal compounds as starting point and few range of fungi have been screened in this bioconversion activity. This research has been focused on the structural modifications of steroids mediated by fungi, in order to investigate the effect of culture on substrate. In the study we have chosen to investigate the effect of Trichothecium roseum and SSW endophyte and it has been carried out for the first time. Biotransformation of tibolone by fungal Trichothecium roseum yielded five metabolites. The hydroxylations were mainly undergone in rings A, B and C, especially at C-3, C-6 and C-12 positions. The structural modification of an antiinflammatory drug, prednisolone by a marine endophytic fungus coded as SSW isolated from marine algae sea weed was reported for the first time. The biotransformation led to the formation of a known compound named 20p-hydroxy prednisolone. Transformation of 21-acetylprednisolone was done in parallel with prednisolone in order to see the effect of side chain of prednisolone in biotransformation. Endophytic fungus Penicilium lapidosum (SSW) also gave a positive result on deacetylation of 21-acetylprednisolone to prednisolone in two days fermentation and finally transformed to 20P-hydroxyprednisolone after six days fermentation. The absolute configuration of 20p-hydroxyprednisolone was also confirmed first time by both experimental and calculated chemical coupling constants and ECD spectra. The isolation and identification of marine endophytic fungus SSW was successfully performed in this study. The SSW strain sequence was blasted in National Centre for Biological Information (NCBI) Genebank. The blast showed 99% homology with Penicilium lapidosum database sequence.